Analisis Kolaborasi Dan Team Kerja Apron Movement Control Dalam Management Parking Stand Di Bandar Udara Internasional Yogyakarta - Tri Ananda Parsaulian Napitupulu; Andi Syaputra (Institut Nalanda, 2024)
This study aims to find out: Parking Stand Management in Apron Movement Control is a responsible task in providing services and supervision for regulating aircraft parking in the apron area. In Parking Stand Management, collaboration and work teams are needed to form communication about work success in Parking Stand Management, because without collaboration and work teams, problems may occur in completing tasks at the parking stand, such as parking stand operational errors, The author used a descriptive qualitative method in solving existing problems. This research carried out data collection through interviews, observation, documentation and literature study. Based on observations in the field with presentation in the form of descriptive sentences with 3 steps, namely data reduction, data presentation, and drawing conclusions. The results of this research were obtained by explaining that AMC officers have a very important role in Parking Stand Management to provide smooth, safe and secure aircraft in the apron area in accordance with the applicable SOP. And at Yogyakarta International Airport, obstacles were found such as heavy flight traffic at YIA, handling obstacles in the apron area, and checking vehicles, people and facilities, so that errors in parking stand management could be monitored for operational activities, so there was a need for collaboration and team work. to regulate the allocation of aircraft parking at the parking stand and stabilize the work process of the AMC as well as collaborating with other departments to support the AMC's work to run well.